(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
This material responds to a current problem in the teaching-learning process in the students of the Forest Engineering career at the University of Granma. A system of exercises and problems is elaborated with an interdisciplinary professional approach in which situations of forest engineering practice, the Mathematical discipline and the Defense Preparation discipline are linked, the resolution of these problems starts from mathematical modeling and concludes with analysis carried out by students on situations raised that bring them closer to the practice that occurs in the spheres of action of the engineer, favor the understanding of problems of Forest Engineering, the development of mathematical thinking and their preparation for defense in particular. Theoretical, empirical and mathematical statistical methods are used. The problems are directed to the preparation of the students, from the interdisciplinary point of view, which is not possible to find in the current bibliography.